Coalition politics and parliamentary oversight in the European Union - Finke, Daniel; Herbel, Annika (Government & opposition, 2018)
According to the literature, parliamentary scrutiny is either used by the opposition to control the government or by a coalition partner to control the leading minister. Yet, neither the opposition alone nor individual governing parties alone can muster a parliamentary majority to adopt recommendations, resolutions or statements. Therefore, we ask which parties coalesce in co-sponsoring such joint position papers on European Union policy proposals and why. Tying in with the existing literature, we offer three explanations. Firstly, position papers are co-sponsored by so-called ‘policy coalitions’, a group of parties that hold similar preferences on the policy under discussion. Secondly, governing parties form coalitions which support their minister’s position vis-à-vis his or her international partners in Brussels. Thirdly, party groups co-sponsor position papers to counterbalance the leading minister’s deviation from the floor median.On the empirical side, we study the statements issued by committees of the Finnish Eduskunta and recommendations adopted by committees of the German Bundestag over a period of 10 years. Though having similarly strong parliaments, the two countries are characterized by very different types of coalition governments. These differences are mirrored in the observed co-sponsorship patterns.
First published online 19 September 2016
Gesehen am 16.04.2020